2021
DOI: 10.36740/wlek202108125
|View full text |Cite
|
Sign up to set email alerts
|

Painful Subacute Thyroiditis Treatment Approach

Abstract: The aim: The study was aimed to compare the efficiency of intrathyroid steroid injection to oral steroid intake in patients with subacute thyroiditis. Materials and methods: 32 patients with subacute thyroiditis with insufficient result from NSAIDs treatment were randomly divided into two groups. The 1st group received two intrathyroid steroid injections, the 2nd group received oral prednisone. The results of the treatment were evaluated via ultrasound and evaluation of ESR and CRP at 0, 2, 4, 8 and 16 weeks o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“… 9 Intrathyroidal steroid therapy had a shorter duration of disease, with faster results and no side effects when compared with oral, PSN, albeit with further studies required. 10 Low initial doses of PSL like 15 mg/day may help prevent long term steroid related side effects compared to traditional doses of 30–40 mg/day as per Kubota et al 11 and Sato et al 12 An extended tapering period of PSN therapy to 5 mg/day has been shown to reduce recurrence by Mizukoshi et al and Arao et al, 13 , 14 SAT leads to a lower thyroid gland volume in the study by Zhao et al 15 With regards to treatment response and hypothyroidism rate there is essentially no stark difference between low dose steroid therapy (16 mg methylprednisolone) and high dose steroid therapy (48 mg methylprednisolone), suggesting low dose steroid therapy sufficient for the treatment of SAT. 16 The presence of anti TPO antibodies and ibuprofen treatment were found to be independent risk factors for permanent hypothyroidism by Sencar et al 17 Fatourechi et al found steroid therapy more effective in providing relief from acute symptoms with no effect on recurrence or long term hypothyroidism.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… 9 Intrathyroidal steroid therapy had a shorter duration of disease, with faster results and no side effects when compared with oral, PSN, albeit with further studies required. 10 Low initial doses of PSL like 15 mg/day may help prevent long term steroid related side effects compared to traditional doses of 30–40 mg/day as per Kubota et al 11 and Sato et al 12 An extended tapering period of PSN therapy to 5 mg/day has been shown to reduce recurrence by Mizukoshi et al and Arao et al, 13 , 14 SAT leads to a lower thyroid gland volume in the study by Zhao et al 15 With regards to treatment response and hypothyroidism rate there is essentially no stark difference between low dose steroid therapy (16 mg methylprednisolone) and high dose steroid therapy (48 mg methylprednisolone), suggesting low dose steroid therapy sufficient for the treatment of SAT. 16 The presence of anti TPO antibodies and ibuprofen treatment were found to be independent risk factors for permanent hypothyroidism by Sencar et al 17 Fatourechi et al found steroid therapy more effective in providing relief from acute symptoms with no effect on recurrence or long term hypothyroidism.…”
Section: Resultsmentioning
confidence: 99%
“… 18 Intrathyroidal steroid therapy needs further evaluation with different population groups and different body masses. 10 The absence of any large scale studies examining colchicine and Prunella vulgaris in SAT. 19 , 24 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the high-dose steroid treatment was associated with a higher rate of recurrence, whereas no difference was observed in permanent hypothyroidism rates between the two groups [130]. Few investigators have also proposed intrathyroidal steroid injection as an alternative therapeutic approach for SAT, suggesting it could provide a faster, safer, and generally better tolerated approach [131], with most of the patients requiring only one injection to achieve complete curation [131,132].…”
Section: Treatmentmentioning
confidence: 99%